Anemia as a risk factor for lower respiratory tract infection in children of 6 months to 5 years of age - Vashishth, Dhruv; Sharma, Girdhari Lal; Masand, Rupesh (Indian Journal of Child Health, 2019)
Objective: To determine whether anemia is a risk factor for acute lower respiratory tract infections (ALRTI) in children aging6 months–5 years. Materials and Methods: Observational case–control study was performed in 540 children in the age group of6 months–5 years who attended the outpatient and inpatient unit of the department of pediatrics of a tertiary care hospital of Jaipur,during the period from January 2017 to June 2018. 270 cases hospitalized for LRTI who fulfilled the inclusion criteria and 270 healthyage and sex matched controls without any respiratory problems attending outpatient department of the department of pediatrics. Childrenwith congenital anomalies, protein energy malnutrition, tuberculosis, congenital heart defects, HIV, and malignancies were excludedfrom the study. After a detailed history and anthropometric measurements, complete blood count, C-reactive protein, peripheral bloodfilm examination, reticulocyte count, chest skiagram, Mantoux test were done. Iron profile and detailed anemic investigations are doneif hemoglobin level was below 11 g/dl as per the WHO criteria. The sentence in abstract can be framed like this. The norms consideredfor ALRTI were also considered as per defined by the WHO criteria. Results: Male preponderance was observed (55.2%) in the studygroup. Most of the children were